Exploring preservice mathematics teachers' perception of the mathematics teacher through communities of practice - Akkoç, Hatice; Balkanlioğlu, Mehmet Ali; Yeşildere İmre, Sibel (My University, 2016)
This research aimed to analyse the induction experiences of preservice mathematics teachers during their school placements through the lens of communities of practice. The main research question was concerned with how preservice mathematics teachers perceive what constitutes the practice of a professional community of mathematics teachers. A qualitative cross-sectional study was designed. Data collection tools consisted of face-to-face interviews and journals written by participants. Data was analysed using three modes of belonging in communities of practice framework: engagement, imagination and alignment. Findings indicated that participants had valuable observations with regard to professional relationships among mathematics teachers such as openness to exchange of ideas and collaboration. Data also revealed how preservice teachers align themselves with norms and values of university and school cultures. In most cases, preservice teachers endorsed norms of teacher education programs; e.g., they were critical about the traditional methods and the way technology was used in the partnership school. Their beliefs about the importance of confidence, strong subject knowledge and formative assessment were reinforced as a result of their observations in the partnership school.
Keywords: preservice mathematics teachers::initial teacher training::communities of practice::perceptions of the mathematics teacher::professional community of teachers